The Role of China in the Global Spread of the Current Cholera Pandemic - Didelot, Xavier (PLoS Genet, 2015)
Epidemics and pandemics of cholera, a severe diarrheal disease, have occurred since the early 19th century and waves of epidemic disease continue today. Cholera epidemics are caused by individual, genetically monomorphic lineages of Vibrio cholerae: the ongoing seventh pandemic, which has spread globally since 1961, is associated with lineage L2 of biotype El Tor. Previous genomic studies of the epidemiology of the seventh pandemic identified three successive sub-lineages within L2, designated waves 1 to 3, which spread globally from the Bay of Bengal on multiple occasions. However, these studies did not include samples from China, which also experienced multiple epidemics of cholera in recent decades. We sequenced the genomes of 71 strains isolated in China between 1961 and 2010, as well as eight from other sources, and compared them with 181 published genomes. The results indicated that outbreaks in China between 1960 and 1990 were associated with wave 1 whereas later outbreaks were associated with wave 2. However, the previously defined waves overlapped temporally, and are an inadequate representation of the shape of the global genealogy. We therefore suggest replacing them by a series of tightly delineated clades. Between 1960 and 1990 multiple such clades were imported into China, underwent further microevolution there and then spread to other countries. China was thus both a sink and source during the pandemic spread of V. cholerae, and needs to be included in reconstructions of the global patterns of spread of cholera.